1986
DOI: 10.1177/089686088600600410
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of the Spleen: A Complication of Continuous Ambulatory Peritoneal Dialysis

Abstract: A 44-year-old woman on CAPD for 20 months presented with severe intraperitoneal bleeding secondary to rupture of the spleen. On the day of the accident displacement of the Tenckhoff catheter to the left upper quadrant of the abdomen was detected by X-ray. We believe this dislodgement caused the rupture either by direct trauma or erosion of the organ. This complication of CAPD has not been described before. There are no previous reports of rupture of an abdominal organ during chronic peritoneal dialysis. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Here, we describe a clinical case of APR in a patient with amyloid light chain (AL) amyloidosis who was on peritoneal dialysis (PD), and we review all clinical cases of dialysis-related APR or ANR indexed in PubMed up to November 2010 without language restriction. In addition to the present case (PC), we found 21 case reports and 1 series of 3 cases, for a total of 24 cases (2-23). We analyzed demographic characteristics, clinical presentation, diagnostic process, and management, focusing on differences between patients on PD and those on hemodialysis (HD).…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Here, we describe a clinical case of APR in a patient with amyloid light chain (AL) amyloidosis who was on peritoneal dialysis (PD), and we review all clinical cases of dialysis-related APR or ANR indexed in PubMed up to November 2010 without language restriction. In addition to the present case (PC), we found 21 case reports and 1 series of 3 cases, for a total of 24 cases (2-23). We analyzed demographic characteristics, clinical presentation, diagnostic process, and management, focusing on differences between patients on PD and those on hemodialysis (HD).…”
mentioning
confidence: 50%
“…Median age was 55 years in patients on PD (range: 43 - 74 years) and 51 years in those on HD (range: 22 - 70 years; p = 0.43); men represented 50% of the patients on PD and 76% of those on HD; and mean time on dialysis was 28 ± 30 months and 40 ± 44 months for patients on PD and HD respectively (p = 0.5). Nephroangiosclerosis because of hypertension (2,13,17,18,22) or diabetes (6,11) was the cause of ESRD in 6 patients, renal amyloidosis in 5 (5,9,12,19, PC), chronic glomerulonephritis in 2 (10,20), urolithiasis in 1 (13), lupus nephropathy in 1 (23), and chronic allograft nephropathy in 1 (7). The cause was unavailable in 8 patients (3[cases b, c, d],4,8,16,21).…”
Section: Discussionmentioning
confidence: 99%
“…Aubrey-Bassler et al identified 112 cases of ASR occurred after medical procedures [5], among which one case was attributed to the displacement of a continuous ambulatory peritoneal dialysis catheter [6]. From 1986 to 2016, a total of eight cases of ASR had been reported in patients undergoing peritoneal dialysis (Table 3) [6][7][8][9][10][11][12]. Among these, three cases were due to amyloidosis: one case was caused by splenic infarction and another case was secondary to chronic myelogenous leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…In one case, splenectomy was performed and a pathological examination revealed many lacerations on the surface of the spleen [6]. The patient had worked for many hours using a manual sewing machine.…”
Section: Discussionmentioning
confidence: 99%